Effect of conservation tillage on C and N fractions in soils having different textures under rice-wheat cropping system in Haryana - KUMARI, KIRAN; MEENAKSHI; DEVRAJ; SINGH, NARENDER; CHAUDHARY, ANKUR (Journal of Soil and Water Conservation, 2026)
A difference in management practices often result in differences in biological, chemical and physical properties of soil which in turn, result in functional quality of the soil. The information about soil organic carbon and organic nitrogen fractions under different tillage systems is essential for sustainability of agricultural systems. Keeping this in view, the long-term impact of zero tillage in wheat under ricewheat cropping system at farmers’ fields was evaluated during 2020-2021 for monitoring changes in different fractions of soil organic carbon and nitrogen, and wheat productivity parameters in three texturally different soils (sandy loam, clay loam and loamy soil) of Haryana. The zero tillage practice in wheat increased the organic carbon content and carbon stock compared with conventional tillage in soils. Reduction in the intensity of tillage from conventional to zero resulted in decrease in bulk density of sub- surface soil. The zero tillage increased dissolved organic carbon, microbial biomass carbon light and heavy fractions of carbon in soils at both the depths. The light and heavy fraction carbon values were observed to be lower in lighter textured soil which increased with increase in fineness of the texture. The total nitrogen was highest in clay loam under zero tillage at 0-15 cm depth as compared to conventional tillage. Total hydrolysable nitrogen was found highest in clay loam followed by loam and sandy loam soils. Highest values of non-hydrolysable nitrogen, amino acid nitrogen, and hydrolysable ammonium nitrogen were observed in zero tillage practice as compared to conventional practice. The practice of zero tillage found to be effective in increasing yield of wheat in fine textured soils as compared to coarse textured. The results of the study suggested that the practice of zero tillage in wheat under rice-wheat cropping system may be adopted for sustaining the productivity of the cropping system